First-in-human phase I clinical trial of the NY-ESO-1 protein cancer vaccine with NOD2 and TLR9 stimulants in patients with NY-ESO-1-expressing refractory solid tumors - Ishihara, Mikiya (Cancer Immunol Immunother, 2020)
Cholesteryl pullulan (CHP) is a novel antigen delivery system. CHP and New York esophageal squamous cell carcinoma 1 (NY-ESO-1) antigen complexes (CHP-NY-ESO-1) present multiple epitope peptides to the MHC class I and II pathways. Adjuvants are essential for cancer vaccines. MIS416 is a non-toxic microparticle that activates immunity via the nucleotide-binding oligomerization domain 2 (NOD2) and TLR9 pathways. However, no reports have explored MIS416 as a cancer vaccine adjuvant. We conducted a first-in-human clinical trial of CHP-NY-ESO-1 with MIS416 in patients with NY-ESO-1-expressing refractory solid tumors. CHP-NY-ESO-1/MIS416 (μg/μg) was administered at 100/200, 200/200, 200/400 or 200/600 (cohorts 1, 2, 3 and 4, respectively) every 2 weeks for a total of 6 doses (treatment phase) followed by one vaccination every 4 weeks until disease progression or unacceptable toxicity (maintenance phase). The primary endpoints were safety and tolerability, and the secondary endpoint was the immune response. In total, 26 patients were enrolled. Seven patients (38%) continued vaccination in the maintenance phase. Grade 3 drug-related adverse events (AEs) were observed in six patients (23%): anorexia and hypertension were observed in one and five patients, respectively. No grade 4–5 drug-related AEs were observed. Eight patients (31%) had stable disease (SD). Neither augmentation of the NY-ESO-1-specific IFN-γ-secreting CD8(+) T cell response nor an increase in the level of anti-NY-ESO-1 IgG1 was observed as the dose of MIS416 was increased. In a preclinical study, adding anti-PD-1 monoclonal antibody to CHP-NY-ESO-1 and MIS416 induced significant tumor suppression. This combination therapy is a promising next step. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00262-020-02483-1) contains supplementary material, which is available to authorized users.